Job Satisfaction Towards Employee Loyalty In Hospitals - Osnawati Marsaoly; Arif Mustofa; Liskha Ayuningrum; M Awaluddin; Muhammad Asdar (Universitas Cahaya Prima, 2025)
This study aims to analyze the influence of job satisfaction on employee loyalty in hospitals through a qualitative literature review. In the context of healthcare, job satisfaction is a crucial factor determining employee loyalty and performance. The study reviews national studies published between 2020 and 2025, focusing on factors such as compensation, leadership style, work motivation, organizational culture, and career development. The results indicate that job satisfaction is positively and significantly related to employee loyalty. Factors such as compensation, leadership style, motivation, organizational culture, and career development opportunities have been shown to influence job satisfaction levels, which ultimately impact employee loyalty to the hospital. Furthermore, transformational leadership and work motivation act as supporting factors that strengthen the relationship between satisfaction and loyalty. Therefore, increasing job satisfaction through inspirational leadership strategies, fair reward systems, and sustainable career development can be a strategic step in building employee loyalty and improving overall hospital organizational performance.